Validity and Practicality of Scientific Literacy Assessment Instruments Based on Tornado Physics Enrichment Book - Mulyana, Venny; Desnita, Desnita (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
Scientific literacy prepares citizens to become responsible and sensitive to the problems around them. An instrument that can measure all aspects of scientific literacy is needed to assess students' scientific literacy. This study determined the validity and practicality of the scientific literacy assessment instruments based on the tornado physics enrichment book. Scientific literacy instruments were developed in four aspects: context, competence, and knowledge (in the form of essay tests), and attitudes toward science (self-assessment questionnaires). This study was research and development. The ADDIE development model uses stages such as analysis, design, development, implementation, and evaluation. With valid categories, the expert validation for each aspect is content 0.81, construct 0.86, and language 0.85. With very practical criteria, a practicality value of 83.7% was obtained in the data analysis for the practicality test for teachers. With very practical criteria, the practicality test data analysis on students yielded a practicality value of 85.3%. The study results concluded that the scientific literacy assessment instrument developed as a result of the test was valid and practical. The results of this study are expected to be used as an assessment instrument to measure students' scientific literacy abilities.